(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Alcohol and Substance Use Disorder (ASUD) is a complex and pervasive public health issue globally. While efforts to address substance abuse have led to an advancement in prevention, treatment, and harm reduction strategies, relapses, which is different than the ’lapse’ or ’slip’ as it involves a more extended and excessive return to substance use after a period of voluntary abstinence, has been seen as a significant challenge in recovery treatment. Purpose: Exploring the causes and consequences of Relapse and repetitive Relapse of individuals with ASUD in Kathmandu, Nepal, is the primary objective of this research, followed by expanding the understanding of repetitive relapse and identifying its prevention strategies. Methods: This research adopted a qualitative methodology. Data are collected between August and October 2024. The collected data were analysed using a thematic analysis approach. The data were collected through in-depth interviews with eight participants (six males and two females), followed by a focus group discussion, after a preliminary analysis of information obtained from in-depth interviews. The respondents have been selected through purposive sampling, by identifying the information-rich informants who have experienced repetitive relapses but are sober at present. Findings: Peer pressure, curiosity, stemming from social circles, including spousal encouragement, interactions, and reservations about abstaining and pleasure-seeking behaviours, are the key influential factors of addiction and relapse. Furthermore, an individual’s misconception of one’s ability to control substance use patterns, exacerbated negligence, feeling of hopelessness, and disregard for consequences, were the triggering factors of repetitive relapse. The implications of repetitive relapses are, but not limited to: individuals isolating themselves, deepening the cycle of regret into remorse, compounded by psychological victimisation of oneself, including - attempts to suicide, and a perceived lack of coping capacity as well as undergoing a soul-crushing experience, numbed senses, dysfunctional brain’s reward system, and hopelessness. Conclusion: The causes of relapses and repetitive relapses are variable across the respondents, but the implications of addiction, relapse, and repetitive relapses are similar, although the phases of addiction and increased frequency of relapse accelerated the intensity of suffering, which is critically serious from a treatment and recovery perspective. The findings contribute to understanding relapse’s psychological and social triggers and their severe consequences, which is valuable for both academic and clinical audiences. Keywords: Cause and consequences, Recovery, Rehabilitation, Substance abuse, Triggering factors JEL Codes: I12, I18, Z13, I31